2016
DOI: 10.1002/1873-3468.12447
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the interaction of human p97 N‐terminal domain and SHP motif in Derlin‐1 rhomboid pseudoprotease

Abstract: The interaction of the rhomboid pseudoprotease Derlin-1 and p97 is crucial for the retrotranslocation of polyubiquitinated substrates in the endoplasmic reticulum-associated degradation pathway. We report a 2.25 Å resolution structure of the p97 N-terminal domain (p97N) in complex with the Derlin-1 SHP motif. Remarkably, the SHP motif adopts a short, antiparallel β-strand that interacts with the β-sheet of p97N-a site distinct from that to which most p97 adaptor proteins bind. Mutational and biochemical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 40 publications
(51 reference statements)
1
22
0
Order By: Relevance
“…Like other rhomboid proteases, Rhbdl4 is an intramembrane protease, its active site buried in the lipid bilayer where one of its function is the release of growth factors [ 122 ]. The protease has been shown to efficiently form a ternary complex with p97 and K48-linked polyubiquitin [ 123 , 124 ]. A VBM, whose interaction with p97 has been comprehensively characterized biochemically, is located at its C-terminus, next to a ubiquitin-interacting motif [ 123 , 124 ].…”
Section: P97 and Its Cofactorsmentioning
confidence: 99%
“…Like other rhomboid proteases, Rhbdl4 is an intramembrane protease, its active site buried in the lipid bilayer where one of its function is the release of growth factors [ 122 ]. The protease has been shown to efficiently form a ternary complex with p97 and K48-linked polyubiquitin [ 123 , 124 ]. A VBM, whose interaction with p97 has been comprehensively characterized biochemically, is located at its C-terminus, next to a ubiquitin-interacting motif [ 123 , 124 ].…”
Section: P97 and Its Cofactorsmentioning
confidence: 99%
“…The initial crystal structure of full-length p97 in complex with the SHP motif of UFD1 revealed that the motif adopts a mostly extended, yet slightly bent conformation, and binds at the periphery of the C-terminal α+β subdomain (Nc, aa 112–186) of the N domain, in direct vicinity of the ND1 linker (Hänzelmann and Schindelin, 2016a). Subsequently, a high-resolution structure of the N domain in complex with the UFD1-SHP using an N domain-SHP fusion protein (Le et al, 2016) (Figures 4B,C) as well as the N domain structure with the SHP of the DERLIN1 (DER1) rhomboid pseudoprotease (Lim et al, 2016b) (Figure 4C) were determined. The SHP motif forms a random coil interrupted by a small two amino acid long β-sheet, which associates with the central four-stranded β-sheet, thereby extending it to a five-stranded antiparallel β-sheet.…”
Section: Molecular Insights Into P97 Cofactor Diversitymentioning
confidence: 99%
“…In addition, an adjacent α-helix stabilizes the complex. The motif thus binds in a hydrophobic binding pocket and is stabilized between one of the β-strands and this α-helix, which together are arranged into a β-β-α super-secondary structure, a well-known binding mode mediating protein-protein interactions (Lim et al, 2016b). The two strictly conserved glycine residues (GxG) generate a sharp kink in the middle of the SHP motif, thereby enabling the bending of the motif upon binding to the N domain.…”
Section: Molecular Insights Into P97 Cofactor Diversitymentioning
confidence: 99%
See 2 more Smart Citations